Tin Microcrystals Synthesized by Thermal Chemical Vapor Deposition in a Hydrogen-Reducing Atmosphere - Ham, Daseul; Jeong, Won; Kang, Hyon Chol (Korean Journal of Metals and Materials, 2019)
We demonstrate a synthetic route to high-quality Sn microcrystals using thermal chemical vapor deposition (CVD) in a hydrogen-reducing atmosphere. During thermal CVD with SnO2 powder, a mixture of Ar and H2 (4%) gases was used as a carrier gas to maintain a hydrogen reduction environment. Hydrogen maintained a reduction environment throughout the thermal CVD process. Samples were prepared at temperatures of 800, 900, and 1000 °C. The structural properties of the Sn microcrystals were determined using synchrotron X-ray diffraction (XRD), transmission electron microscopy, and micro-Raman spectroscopy. In particular, the atomic position order in both the out-of-plane and in-plane directions was determined through high-resolution XRD measurement in a four-circle geometry. We found that at temperatures greater than 800 °C the supersaturation of Sn and O vapors induces the formation of microcrystals by self-assembly process without additional metallic seeds. As determined by the energy dispersive X-ray analysis, oxygen atoms and/or vapor were simultaneously reduced by hydrogen gas, resulting in the formation of Sn crystals rather than Sn oxide crystals. We also found that the Sn microcrystals were mostly strain-free singlecrystalline and of high quality with extremely low mosaicity. The order of the atomic positions in both the out-of-plane and in-plane directions was comparable to that of single-crystalline sapphire. KCI Citation Count: 1